Design an interactive learning model: using persuasive technology to learn children Arabic alphabets - Abusafia, Alaa H. (2013)
The rapid development of courseware technology has achieved a supportive impact in the field of education. Using interactive learning in the courseware is a more hands-on, real-world process of relaying information to children. Despite interactive learning motivates children to explore and learn effectively, there is still a need to exploit it in teaching children Arabic alphabets. The aims of this project are to understand the concept, steps, principles and impacts of interactive learning using Persuasive Technology in the learning process then design an interactive learning model to teach children who aged between 18 months and 4 years old Arabic alphabets. In order to reach this aims, Persuasive Technology was used to understand the children’s behaviour and encourage them to learn Arabic alphabets since target age. An interactive learning model was proposed by integrating four different means of technology to support the learning process which are; Flashcards, Persuasive Design, Cognitive Theory of Multimedia Learning (CTML) and Multimedia Principles. The effectiveness and usability of this model was evaluated by developing Arabic alphabets courseware and distributed it between numbers of young children. The effectiveness was assessed through pre and post testing while the usability testing based on five factors of usability which are; motivation, learning, memorability, performance and effectiveness. These factors were assessed by using a questionnaire for the children’s parents who have observed their children behaviour and answered the questions. Furthermore, a video observation was recorded to ensure the accuracy and reliability of the results. Analysing this information showed that, the interactive learning model can influence effectively in persuading young children to learn Arabic alphabets and this model provides an alternative way to motivate young children to learn Arabic alphabets before learn the IQRA technique.